Research on Frequent Failures of Pilot Solenoid Valve of Emergency Diesel Engine in Nuclear Power Plant. Issue 1 (1st March 2022) - Fu, Jiang; Pan, Weiwei; Qin, Qiang; An, Kang; Wang, Meng
Abstract: The working pressure of the start-up compressed air pilot solenoid valve is 40bar when it starts, it is an important part of the emergency diesel air start system of nuclear power plants. Since the operation of the nuclear power plant, it has been found that the start-up compressed air pilot solenoid valve has more frequent failures, the failure modes are air leaks and jams. The start-up compressed air pilot solenoid valve are all solenoid valves of the same type, the manufacturer is MABO, the model is MV320V DN20 G34 NC. Once the start-up compressed air pilot solenoid valve fails, it will affect the reliability and availability of the diesel engine's start-up air system, directly cause the diesel engine to fail to start. Through a series of tests, the jamming and air leakage failures in the use of the start-up compressed air pilot solenoid valve are tested and analyzed. The reasons for the frequent air leakage and jamming of the starting compressed air pilot solenoid valve are determined, effective improvement plans are proposed, such as changing to another type of grease, adding the solenoid spool guide ring and return spring, improving the spool structure, increasing the diameter of the pilot valve and coil power, etc.. After analysis and demonstration, it is further clarified that the reasons for the leakage and jamming of the pilot solenoid valve are clear, the improvement plan is effective. The results show that the improved program obtained through research has laid a foundation for solving the problem of frequent leakage and jamming of the pilot solenoid valve.